Evaluation of Drinking Water Quality Based on Quality Standards as a Guarantee of Food Safety in Serang Regency - Angelina Sondang Purba; Afny Nur Pratiwi; Tetin Sunari; Abu Salim; Roch Galih Saktya Candraningrum (Journal of Food and Agricultural Product, 2026)
Drinking water is a basic human need that must meet quality standards to ensure its safety for consumption. Water contamination can occur due to human activities and environmental factors that may reduce water quality. This study aimed to evaluate the quality of drinking water in Serang Regency based on physical, chemical, and microbiological parameters. Fifteen drinking water samples were analyzed in the lab using MPN method for microbiological parameters (Coliform and Escherichia coli), as well as physical and chemical parameters (nitrite, nitrate, pH, turbidity, iron content, taste, and odor). The results showed that all samples met the standards for chemical parameters, as well as physical parameters including pH, taste, and odor. However, several samples had turbidity values exceeding the limit set by the Minister of Health Regulations, although still within the WHO’s standard limit. Microbiological analysis revealed the presence of coliform bacteria and Escherichia coli in several samples, indicating that they didn’t meet the required standards. In conclusion, the majority of Serang Regency's drinking water samples satisfied physical and chemical quality standards, while some samples did not meet microbiological requirements. This suggests that continuous monitoring and appropriate management of drinking water quality are necessary to guarantee public health safety. Keywords: drinking water, quality standard, food safety